Paracoccidioidomicosis perianal asociada a lepra lepromatosa: Presentación de un caso clínico Perianal paracoccidioidomycosis associated with lepromatous leprosy: A clinical case report - M A Reyes; J Weidmann; M V Guardati; M G Díaz; E Carbó Amoroso; J Henares; M E Nardín; E Méndez; J L Iribas (Asociación Argentina de Dermatología, 2008)
Se presenta el caso de un paciente alcoholista con una ulceración perianal y manifestaciones cutáneas de enfermedad de Hansen. La biopsia de la lesión perianal y otros estudios arribaron al diagnóstico de una forma diseminada de paracoccidioidomicosis, así como también las biopsias cutáneas y los estudios baciloscópicos fueron diagnósticos de lepra lepromatosa. La respuesta a la terapéutica fue satisfactoria con desaparición de las lesiones cutáneas. La disminución de la respuesta inmunológica celular genera un terreno propicio para la infección de estos gérmenes y al compartir área endémica la asociación entre ambas patologías puede ocurrir. Lepra and Paracoccidioidomycosis are endemic diseases in Argentina. We report a case of a patient with an unusual perianal ulceration and cutaneous manifestations of Hansen's disease. The biopsy of perianal lesion and subsequent studies revealed a disseminated form of paracoccidioidomycosis, as well as skin biopsy and baciloscopic finding diagnostic of Lepromatous Leprosy. The main portal of entry of paracoccidioides is the lung. Hematogenous dissemination of the fungus may occur at this time, with the establishment of metastatic foci in any organ. Anal and perianal lesions are present only in 1.3 to 2.4% of the patients. The pathogenesis of anal lesions remains unclear, it may be secondary from a systemic or a local disease. The patient response to the therapeutic was notable, with disappearance of lesions up to the third month of started itraconazole orally 400 mg/day leading just atrophy scars in perianal areas. The treatment of Hansen's disease was made according to OMS guidelines for multibacillary disease.